2010
DOI: 10.1007/s00125-010-1943-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipid peroxidation products and oxidative stress in activation of the canonical wingless-type MMTV integration site (WNT) pathway in a rat model of diabetic retinopathy

Abstract: Aims/hypothesisOur recent studies suggest that activation of the wingless-type MMTV integration site (WNT) pathway plays pathogenic roles in diabetic retinopathy and age-related macular degeneration. Here we investigated the causative role of oxidative stress in retinal WNT pathway activation in an experimental model of diabetes.MethodsCultured retinal pigment epithelial cells and retinal capillary endothelial cells were treated with a lipid peroxidation product, 4-hydroxynonenal (HNE), and an antioxidant, N-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 46 publications
2
70
0
Order By: Relevance
“…We injected 2F1 antibody, which binds to the ligand-binding domain of LRP6 and blocks WNT pathway activation [30], into Akita mice; the same dose of non-specific mouse IgG was used as the negative control. Western blot analysis showed that the accumulation of β-catenin in the kidneys of Akita mice was Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We injected 2F1 antibody, which binds to the ligand-binding domain of LRP6 and blocks WNT pathway activation [30], into Akita mice; the same dose of non-specific mouse IgG was used as the negative control. Western blot analysis showed that the accumulation of β-catenin in the kidneys of Akita mice was Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As there are multiple WNT ligands and FZD receptors, but only two co-receptors-LRP5 and LRP6-we used an antibody specific for the ligand-binding domain of LRP6 to inhibit WNT signalling [30]. Injection of this antibody into Akita mice inhibited the activation of the WNT pathway and ameliorated diabetic nephropathy as shown by fibrogenic factor production, extracellular matrix accumulation and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt pathway is essential for the early development of eukaryotic organisms and is involved in cell proliferation, differentiation, and oncogenesis (Kitazoe et al, 2010). Lipid peroxidation products activate the canonical Wnt pathway through oxidative stress (Zhou et al, 2011). The insulin signaling pathway controls the synthesis and accumulation of lipids in the mammalian liver.…”
Section: Discussionmentioning
confidence: 99%
“…Similar or higher concentrations have been used in the past by others and by ourselves for studies on various cell types. 14,15,31,[35][36][37][38][39] Cell Viability Assay …”
Section: Ldl Concentrations In Cell Culturementioning
confidence: 99%